Strikingly diverse reactivity of structurally identical silylene and stannylene12. Issue 20 (9th May 2017) - Parvin, Nasrina; Dasgupta, Rajarshi; Pal, Shiv; Sen, Sakya S.; Khan, Shabana
Abstract : The divergent reactivity of structurally similar silylene and stannylene was observed with coinage metal halides. While the former tends to form an adduct, the latter undergoes ligand exchange reaction. Abstract : The reactivity of structurally identical silylene and stannylene [PhC(N t Bu)2 EN(SiMe3 )2 ] (E = Si (1 ) and Sn (2 )) towards coinage metals has been explored. While1 has the propensity to form an adduct with coinage metals (4 and5 ), 2 undergoes a ligand exchange reaction with copper halides and silver triflate leading to PhC(N t Bu)2 SnX (X = Br (6 ), Cl (7 ), and OSO2 CF3 (8 )) with concomitant formation of [M{N(SiMe3 )2 }] (M = Cu, Ag). However, with AgSbF6 both1 and2 led to ion pairs, 9 + ·SbF6 – and 10 + ·SbF6 – displaying weaker Ag⋯·F interactions in the latter.